Harold Tucker Webster autobiographical note - Webster, Harold Tucker, 1885-1952.
Signed typescript concerning Webster's life as a cartoonist.
Cartoonist.
Collection material in English.
Forms part of: Miscellaneous Manuscript collection.
Keywords: Cartooning; Cartoonists